A kind of electrolyte for high voltage lithium metal battery and preparation method thereof
By introducing lithium fluoride and lithium nitrate into the electrolyte of high-voltage lithium metal batteries, a solid electrolyte interface film rich in inorganic substances is solved, and efficient lithium ion diffusion and battery stability are achieved.
Patent Information
- Application Number
- CN202211138546.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-09-19
AI Technical Summary
The cycling performance of high-voltage lithium metal batteries is limited by the unstable metal lithium/electrolyte interface, especially the low lithium ion diffusion coefficient, low resistivity and low mechanical strength of solid electrolyte membranes, resulting in a sharp increase in lithium dendrites growth and battery impedance.
By introducing dissolved lithium fluoride and lithium nitrate as additives into the electrolyte solution, the electrolyte solution induces the formation of a solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganic substances on the surface of the metal lithium negative electrode, enhancing the electronic insulation, mechanical strength and lithium ion diffusion ability of the interface.
A solid electrolyte interface film with high ion diffusion ability, high resistivity and high Young's modulus has been achieved, which significantly improves the circulation performance and Coulomb efficiency of lithium metal batteries, and reduces the growth of lithium dendrites and the risk of thermal runaway in the battery.
Smart Images

Figure CN115395098B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-voltage lithium metal batteries and relates to an electrolyte. Specifically, a high-voltage lithium metal battery electrolyte and a preparation method thereof are provided. The electrolyte can induce the generation of a solid electrolyte interface film rich in inorganic substances to enhance the cycle performance of the high-voltage lithium metal battery. Background Art
[0002] High-voltage lithium metal batteries are considered one of the most promising candidates for energy density exceeding 400Wh / Kg. Although they have high energy density, their commercial applications are greatly challenged. The most important contradiction is the unstable metal lithium / electrolyte interface: due to the uneven intrinsic surface of metal lithium, lithium deposition tends to occur where the current density is concentrated and eventually forms lithium dendrites. At the same time, due to the extremely high reactivity of metal lithium, fresh metal lithium will spontaneously react with the electrolyte and form a solid electrolyte membrane (SEI) that can pass lithium ions but is electronically insulated. High-voltage lithium metal batteries refer to lithium secondary batteries with an operating voltage exceeding 3V and mainly using ester electrolytes, including: Li∥LiFePO4, Li∥LiNi x Co y Mn 1-x- y O2 and other lithium secondary batteries with higher voltage platforms; however, the solid electrolyte membrane naturally generated by ester electrolytes faces key challenges such as low lithium ion diffusion coefficient, low resistivity, and less than ideal mechanical strength, which makes its solid electrolyte interface membrane easy to break and causes fresh metallic lithium to be directly exposed to the electrolyte environment, which in turn leads to the uncontrollable growth of lithium dendrites and a sharp increase in battery impedance due to the gradual drying of the electrolyte; when lithium dendrites pierce the diaphragm and cause the battery to short-circuit, the battery will face the risk of thermal runaway; therefore, the key to achieving a stable metallic lithium / electrolyte interface in an ester environment is to achieve an ideal solid electrolyte interface membrane with high lithium ion diffusion coefficient, high resistivity, and high mechanical strength.
[0003] At present, a variety of modification schemes have been proposed, such as optimizing the electrolyte system, modifying the artificial solid electrolyte interface membrane, alloying lithium metal, and three-dimensional current collector, and the electrochemical properties of the metal lithium negative electrode have been modified to varying degrees. Among them, optimizing the components of the solid electrolyte interface membrane by electrolyte additives is an effective modification strategy, which can not only effectively enhance the performance of the solid electrolyte membrane and thus effectively enhance the interfacial stability of the metal lithium negative electrode, but also its experimental modification strategy is easier to commercialize. In the naturally generated solid electrolyte interface membrane, lithium fluoride, as a key component, not only effectively enhances the mechanical strength of the solid electrolyte interface membrane, but also improves the electronic insulation of the solid electrolyte interface membrane; therefore, achieving a solid electrolyte interface membrane rich in lithium fluoride is considered to be one of the effective means to stabilize the metal lithium / electrolyte interface; however, commercial lithium fluoride is difficult to dissolve directly in ether electrolytes, resulting in the inability to form an ideal solvation structure to enhance the electrochemical performance of the solid electrolyte membrane of the metal lithium negative electrode. At the same time, lithium nitrate is widely used as an additive in lithium-sulfur batteries based on ether electrolytes due to its small lithium ion diffusion barrier. However, lithium nitrate cannot be directly dissolved in ester electrolytes, which results in lithium nitrate being unable to improve the solvation structure of ester electrolytes and thus enhance the lithium ion diffusion performance of the metal lithium solid electrolyte interface. Therefore, it is very important to develop a method that can effectively dissolve lithium nitrate in ester electrolytes. Summary of the invention
[0004] The purpose of the present invention is to provide an electrolyte for a high-voltage lithium metal battery and a preparation method thereof in order to improve the cycle performance of the high-voltage lithium metal battery and promote its commercial application. The present invention simultaneously introduces soluble lithium fluoride and lithium nitrate as additives, so that the electrolyte can induce the formation (spontaneous reaction) of a solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganic substances on the surface of the metal lithium negative electrode, wherein lithium fluoride can effectively enhance the electronic insulation of SEI to prevent the generation of electron tunneling and enhance the rigidity of SEI, and lithium nitrate can induce the formation of LiN with a lower lithium ion diffusion barrier. x O y It also accelerates the transport of lithium ions in SEI, thereby making the solid electrolyte interface membrane rich in lithium fluoride and lithium nitrate inorganic substances have ideal characteristics of high ion diffusion capacity, high resistivity and high Young's modulus.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] An electrolyte for a high-voltage lithium metal battery, composed of a lithium salt, a solvent, and an additive; characterized in that the additive includes: a first additive and a second additive, the first additive is submicron lithium fluoride with a cubic structure, and the second additive is lithium nitrate.
[0007] Furthermore, the electrolyte for high-voltage lithium metal batteries is characterized in that the electrolyte is not only applicable to high-voltage lithium metal batteries, but also to conventional voltage lithium metal batteries.
[0008] Furthermore, the content of the lithium salt is 0.1-1 mol / L, the content of the first additive is 1-20 wt %, and the content of the second additive is 1-10 wt %.
[0009] Furthermore, the first additive (having cubic submicron lithium fluoride) is prepared by the following method: using ammonium fluoride and / or ammonium tetrafluoroborate as a fluorine source, using lithium nitrate and / or lithium hydroxide as a lithium source, using ethylene glycol as a dispersant, uniformly dispersing the fluorine source and the lithium source in ethylene glycol at a molar ratio of 1:1, and reacting at 100°C to 120°C under an inert atmosphere for 60s to 100s, and finally centrifugally washing and drying to obtain submicron lithium fluoride having a cubic structure.
[0010] Furthermore, it is characterized in that the second additive (lithium nitrate) is prepared by the following method: lithium nitrate is dried at 100°C to 150°C for 3h to 10h to completely remove crystal water, and then dissolved in cyclopentane sulfone and / or dimethyl ether to form a second additive, and the solution concentration of the second additive is 1 to 2.5 mol / L.
[0011] Furthermore, the lithium salt is one or a mixture of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0012] Furthermore, the solvent is one or a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).
[0013] Furthermore, the method for preparing the electrolyte for the high-voltage lithium metal battery comprises the following steps:
[0014] S1: dissolving the lithium salt in a solvent by magnetic stirring, and then standing at room temperature to obtain a mixed solution;
[0015] S2: adding the first additive and the second additive to the mixed solution in proportion, stirring them magnetically to dissolve them, and then standing them at room temperature to obtain the target electrolyte.
[0016] Based on the above technical solution, the beneficial effects of the present invention are:
[0017] 1. The present invention provides an electrolyte for a high-voltage lithium metal battery. First, submicron lithium fluoride with a cubic structure is successfully prepared as a first additive. The lithium fluoride is essentially different from the existing irregularly morphological micron commercial lithium fluoride and can be directly dissolved in an ether electrolyte. Secondly, lithium nitrate that cannot be directly dissolved in an ester electrolyte is first dissolved in cyclobutane sulfone and / or dimethyl ether to form a second additive that can be dissolved in an ether electrolyte. Finally, the first additive and the second additive are simultaneously introduced into the ether electrolyte for synergistic modification. The electrolyte for a high-voltage lithium metal battery in the present invention can induce the generation (spontaneous reaction) of a solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganics on the surface of a metallic lithium negative electrode, wherein lithium fluoride can effectively enhance the electronic insulation of SEI to prevent the generation of electron tunneling and enhance the rigidity of SEI, and lithium nitrate can induce the generation of LiN with a lower lithium ion diffusion energy barrier. x O y And accelerate the transport of lithium ions in SEI, so that the solid electrolyte interface membrane rich in lithium fluoride and lithium nitrate inorganic substances has the ideal characteristics of high ion diffusion capacity, high resistivity and high Young's modulus. In addition, a single additive can only contribute in a single aspect. For example, a single LiF can only improve the electronic insulation of the solid electrolyte interface membrane and excessive LiF will increase the diffusion energy barrier of lithium ions. A single lithium nitrate can only reduce the lithium ion diffusion impedance of the solid electrolyte membrane and has no contribution to the mechanical strength and electronic insulation of the interface membrane. The present invention effectively constructs an ideal solid electrolyte interface membrane with ideal high ion diffusion capacity, high resistivity and high Young's modulus by dissolving lithium fluoride and lithium nitrate together in an ester electrolyte, thereby exerting an ideal synergistic effect. Finally, the electrolyte for high-voltage lithium metal batteries in the present invention is 0.5mA / cm 2 At current densities of 0.5 mAh / cm 2 The coulombic efficiency of more than 98% was achieved at a surface capacity of 1.54 W, providing a new perspective on the study of stable metal lithium / electrolyte interface; furthermore, by combining the high surface capacity LiNi 0.8 Co 0.1 Mn 0.1 O2 was used as the positive electrode, 50μm ultra-thin metallic lithium was used as the negative electrode, and matched with a high-voltage lithium metal battery electrolyte to successfully obtain a high-performance lithium metal secondary battery.
[0018] 2. The preparation process of the electrolyte for high-voltage lithium metal batteries and the two additives therein is simple. The electrolyte and the metal lithium negative electrode spontaneously react to form a solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganic substances, which greatly enhances the stability of the metal lithium / electrolyte interface. It is essentially different from the preparation process of similar interface films in the prior art. That is, the present invention has the advantages of simple preparation, low cost, and good synthesis consistency.
[0019] 3. The electrolyte for high-voltage lithium metal batteries of the present invention is not only applicable to high-voltage lithium metal batteries, but also to conventional voltage lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of the solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganic substances in the present invention.
[0021] Figure 2 This is a SEM image of submicron lithium fluoride with a cubic structure in the present invention.
[0022] Figure 3 The lithium copper battery in Example 1 of the present invention and Comparative Example 1 at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 SEM morphology of lithium deposition at surface capacity.
[0023] Figure 4 The lithium copper battery in Example 1 of the present invention and Comparative Example 1 at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 Cycling performance and Coulombic efficiency diagram at surface capacity.
[0024] Figure 5 The lithium metal symmetric battery in Example 2 of the present invention and Comparative Example 2 at 1 mA / cm 2 The current density is 1mA h / cm 2 Cycling performance and Coulombic efficiency diagram at surface capacity.
[0025] Figure 6 The high voltage lithium metal battery (50 μm thick metal lithium / LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode) cycle performance diagram. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and technical effect of the present invention clearer and more complete, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0027] Example 1
[0028] This embodiment provides a lithium-copper battery, wherein the electrodes on both sides are respectively metal lithium and copper foil, and the electrolyte is composed of lithium salt, solvent, first additive and second additive; specifically:
[0029] The lithium salt is 7.59 g of lithium hexafluorophosphate, and the total solvent is a mixed solvent of 25 ml of dimethyl carbonate and 25 ml of ethylene carbonate;
[0030] The first additive is submicron lithium fluoride with a cubic structure, which is prepared by the following method:
[0031] 2.96 g of ammonium fluoride is used as a fluorine source, 5.51 g of lithium nitrate is used as a lithium source, and diethylene glycol is used as a dispersion liquid. The fluorine source and the lithium source are uniformly dispersed in diethylene glycol, and reacted at 100° C. to 120° C. for 60 seconds under an inert atmosphere, and finally centrifuged and washed and dried;
[0032] The second additive is lithium nitrate, which is prepared by the following method:
[0033] The lithium nitrate is dried at 100° C. to 150° C. for 8 hours to completely remove crystal water, and then dissolved in sulfolane to form a second additive, wherein the concentration of the second additive solution is 2.2 mol / L;
[0034] The high voltage lithium metal battery electrolyte is prepared by the following method:
[0035] The lithium salt is magnetically stirred in a solvent for 24 hours, and then allowed to stand at room temperature to obtain a mixed solution; the first additive and the second additive are then added to the mixed solution in proportion, and magnetically stirred for 24 hours, and then allowed to stand at room temperature to obtain a target electrolyte.
[0036] At the same time, this embodiment also provides comparative example 1: the electrodes on both sides are still lithium metal and copper foil, matched with an unmodified electrolyte, and a lithium-copper battery is assembled under the same process as the embodiment; the unmodified electrolyte is specifically: the lithium salt is 7.59g of lithium hexafluorophosphate, and the total solvent is a mixed solvent of 25ml of dimethyl carbonate and 25ml of ethylene carbonate. The lithium salt is magnetically stirred in the solvent for 24 hours, and then allowed to stand at room temperature to obtain an electrolyte.
[0037] Example 2
[0038] The present embodiment provides a lithium-lithium symmetrical battery, in which electrodes on both sides are lithium metal, and the electrolyte is the same as that in the embodiment 1; at the same time, the present embodiment also provides a comparative example 2: electrodes on both sides are lithium metal, and the same unmodified electrolyte as that in the comparative example 1 is matched, and a lithium-lithium symmetrical battery is assembled under the same process as the embodiment.
[0039] Example 3
[0040] This embodiment provides a high-voltage lithium metal battery, the positive electrode is a high-areal capacity LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode sheet (surface capacity 1.45mAh / cm 2), the negative electrode is a 50 μm thick metal lithium foil, and the electrolyte is the same as that in Example 1; at the same time, this embodiment also provides a comparative example 3: the positive electrode is a high surface capacity LiNi 0.8 Co 0.1 Mn 0.1 The positive electrode sheet is O2, the negative electrode is a 50 μm thick metal lithium foil, and the same unmodified electrolyte as in Comparative Example 1 is matched. A high-voltage lithium metal battery is assembled under the same process as in Example 1.
[0041] Based on the above-mentioned Examples 1 to 3, corresponding tests were performed, and the results are as follows:
[0042] like Figure 1 The figure shows a schematic diagram of a solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganic substances induced by the electrolyte for a high-voltage lithium metal battery of the present invention on the surface of a metal lithium negative electrode (spontaneous reaction); wherein lithium fluoride can effectively enhance the electronic insulation of SEI to prevent the generation of electron tunneling and enhance the rigidity of SEI, and lithium nitrate can induce the generation of LiN with a lower lithium ion diffusion energy barrier. x O y And accelerate the transport of lithium ions in SEI, so that the solid electrolyte interface film rich in lithium fluoride and lithium nitrate inorganics has ideal high ion diffusion capacity, high resistivity and high Young's modulus. A single additive can only contribute in a single aspect, for example, a single LiF can only improve the electronic insulation of the solid electrolyte interface film and excessive LiF will increase the diffusion energy barrier of lithium ions, and a single lithium nitrate can only reduce the lithium ion diffusion impedance of the solid electrolyte film without any contribution to the mechanical strength and electronic insulation of the interface film. The present invention effectively constructs an ideal solid electrolyte interface film with ideal high ion diffusion capacity, high resistivity and high Young's modulus by dissolving lithium fluoride and lithium nitrate together in an ester electrolyte, and exerts an ideal synergistic effect.
[0043] like Figure 2 Shown is a SEM image of the prepared submicron lithium fluoride with a cubic structure. The prepared lithium fluoride has a cubic structure and a diameter of 100 to 300 nm.
[0044] like Figure 3 The results are shown for the lithium copper battery in Example 1 and Comparative Example 1 at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The SEM morphology of lithium deposition under the surface capacity of 100 nm is shown in Figure 1. It can be seen that the lithium deposition corresponding to Comparative Example 1 shows obvious lithium dendrite growth and uneven lithium deposition, and the lithium deposition layer is not dense, while the lithium deposition corresponding to Example 1 does not observe obvious lithium dendrites and the lithium deposition is dense and uniform, which indicates that the inorganic lithium fluoride and LiN on its surface are rich in x O y, Li solid electrolyte interface film + Both transport and structural strength have been enhanced.
[0045] like Figure 4 The results are shown for the lithium copper battery in Example 1 and Comparative Example 1 at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The cycle performance and coulombic efficiency diagram under the surface capacity of 1000 nm is shown in the figure. It can be seen that comparative example 1 experienced serious side reactions and could only stably cycle for 8 cycles, and the coulombic efficiency after 10 cycles was only 83%; while example 1 showed excellent cycle stability and the side reactions were significantly suppressed. After 10 cycles, it was still able to provide a high coulombic efficiency of 97.6%, indicating that the lithium-rich LiF and LiN x O y The solid electrolyte interface film can significantly inhibit the side reactions between metallic lithium and the electrolyte.
[0046] like Figure 5 The results are shown in Example 2 and Comparative Example 2 for lithium metal symmetric batteries at 1 mA / cm 2 The current density is 1mA h / cm 2 The cycle performance and coulomb efficiency diagram under the surface capacity of the battery are shown. It can be seen from the figure that comparative example 2 experiences serious side reactions and can only be stably cycled for 300 hours. This is mainly because its naturally generated solid electrolyte membrane performance is not ideal and cannot effectively suppress interface side reactions. On the contrary, embodiment 2 shows excellent cycle stability and stable cycle for more than 600 hours, showing extremely high interface stability.
[0047] like Figure 6 The high voltage lithium metal battery (50 μm thick metal lithium / LiNi) in Example 3 and Comparative Example 3 is shown. 0.8 Co 0.1 Mn 0.1 The figure shows the cycle performance diagram of the single electrode (O2 positive electrode) at 0.5C / 25℃ (1C=188mA / g). It can be seen that the comparative example 3 shows poor cycle stability, and the capacity retention rate after 40 cycles is only 75%, while the embodiment 3 shows more excellent cycle stability, and the capacity retention rate after 40 cycles is as high as 96%, indicating that the inorganic-rich solid electrolyte interface film in the present invention has extremely strong practical value.
[0048] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. An electrolyte for a high voltage lithium metal battery, comprising a lithium salt, a solvent, and an additive; characterized in that: The additives include: a first additive and a second additive, the first additive is submicron lithium fluoride with a cubic structure, and the second additive is lithium nitrate; The solvent is one or a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC); The lithium salt content is 0.1-1 mol / L, the first additive content is 1-20 wt%, and the second additive content is 1-10 wt%; The second additive is prepared by the following method: drying lithium nitrate at 100°C to 150°C for 3h to 10h to completely remove crystal water, and then dissolving lithium nitrate in cyclopentane and / or dimethyl ether to form a second additive, wherein the solution concentration of the second additive is 1 to 2.5 mol / L.
2. The electrolyte for high voltage lithium metal battery according to claim 1, characterized in that: The lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide, or a mixture of the two or more thereof.
3. The electrolyte for high voltage lithium metal battery according to claim 1, characterized in that: The first additive is prepared by the following method: using ammonium fluoride and / or ammonium tetrafluoroborate as a fluorine source, using lithium nitrate and / or lithium hydroxide as a lithium source, using ethylene glycol as a dispersant, uniformly dispersing the fluorine source and the lithium source in ethylene glycol at a molar ratio of 1:1, and reacting at 100°C to 120°C for 60s to 100s under an inert atmosphere, and finally centrifugally washing and drying to obtain submicron lithium fluoride with a cubic structure.
4. The method for preparing the electrolyte for high voltage lithium metal battery according to claim 1, characterized in that: The following steps are involved: S1: dissolving the lithium salt in a solvent by magnetic stirring, and then standing at room temperature to obtain a mixed solution; S2: adding the first additive and the second additive into the mixed solution in proportion, stirring them magnetically to dissolve them, and then standing them at room temperature to obtain the target electrolyte.
Citation Information
Patent Citations
Metal lithium-based secondary battery electrolyte and application thereof
CN114512722A